GENETIC AND SYSTEMIC TOXICITY INDUCED BY TITANIUM DIOXIDE AND ZINC OXIDE NANOPARTICLES AND THEIR MIXTURE IN SOMATIC AND GERM CELLS OF MICE (2018)
Titanium dioxide (TiO2) and zinc oxide (ZnO) nanoparticles are components of personal care products whose continuous release into the environment may enhance co-exposure, with potential risks to the ecosystem. In vitro studies have shown their potential to induce genetic damage. However, there is dearth of information on in vivo induction of DNA and systemic damage, alongside their interactive effects. This study was designed to investigate genetic and systemic toxicity and mechanism of DNA damage by TiO2 and ZnO nanoparticles and their mixture in mice. Male Swiss mice (=24.0±2.0g; n=80; 6-8 weeks old) were intraperitoneally exposed to distilled water (Control) and 9.4, 18.8, 37.5, 75.0 and 150.0 mg/kg concentrations of each of the nanoparticles and their mixture (1:1) for 5 days (5 mice/group) to assess micronucleus induction and cytomorphological abnormalities in the bone marrow of mice. Haematological parameters [Haemoglobin, Packed Cell Volume (PCV), Red Blood Cell (RBC) and White Blood Cell (WBC) counts] were assessed following standard procedures. Mechanism of DNA damage was evaluated by oxidative stress [Superoxide dismutase (SOD), reduced Glutathione and Malondialdehyde in the liver and kidney] parameters following standard methods. Sperm count, motility, abnormalities and concentrations of Luteinizing Hormone (LH), Follicle Stimulating Hormone (FSH) and Testosterone were evaluated in another group of mice (=30.0±2.0g; n=80; 11-15 weeks old), intraperitoneally exposed with the same nanoparticle concentrations (5 mice/group) at 35-day exposure. Liver, kidney and testis were sectioned for histopathological analysis. The Interaction Factor (IF) of nanoparticle mixture was calculated according to standard method. Data were analysed using descriptive statistics and ANOVA at α0.05. The nanoparticles and mixture induced micronuclei, but significant only for TiO2 (16.8±2.1-53.3±18.5) compared with the control (3.7±0.9). Blebbed, target, hyperchromic and hypochromic erythrocytes were the observed cytomorphological anomalies. The mixture exerted a significant reduction only in the WBC count. In the liver, there was a significant decrease in SOD (unit/mg protein) activities (1.3-1.5; 1.4-2.0; and 1.2-1.6 fold for TiO2, ZnO and mixture, respectively), with increase in Malondialdehyde (nmol/mg protein) levels (1.1-1.7; 1.2-1.8; and 1.7-1.7 fold for TiO2, ZnO and mixture, respectively). In the kidney, there were significant alterations in SOD: 1.2-1.3; and 1.1-1.4 fold decrease for TiO2 and ZnO, respectively; and 1.3-2.0 fold increase for the mixture. While Malondialdehyde levels increased (1.2-1.4; 1.4-1.6; and 1.7-1.9 fold for TiO2, ZnO and mixture, respectively). Both organs showed alterations in reduced Glutathione levels (1.0-1.5 fold decrease for TiO2; 1.0-1.1 fold increase for ZnO and mixture) indicating systemic toxicity. A significant decrease in sperm count and motility; and increase in abnormalities (1.3-8.0; 1.2-2.6; 4.6-12.1 fold for TiO2, ZnO and mixture, respectively), with a concomitant decrease in the serum level of LH and increase in FSH and Testosterone were observed. Hepatocellular and spermatogenic cell necrosis and degeneration of tubular epithelial cells were observed. The IF indicated synergism. Titanium dioxide and zinc oxide nanoparticles and their mixture induced genomic and systemic damage in somatic and germ cells of mice; with the mixture synergistically evoking the highest toxic response. Oxidative stress might be one of the mechanisms of cytogenotoxicity.